Validity of “Negation” and “Interrogatives” in Processability Theory for Iranian EFL Learners - Gholami Rouintani, Amir Hamzeh; Bayat, Abbas; Rajabi, payman (Journal of Modern Languages, 2023)
Processability Theory (PT), which organizes the knowledge base of Second Language Acquisition (SLA), offers an explanation of acquisition sequences. The aim of this paper is to investigate validation of PT for Iranian EFL learners for the acquisition of “negation” and “interrogative” structures across five proficiency levels and compared it with the morpho-syntactic structures model suggested by Pienemann. From the 160 participants having distinct proficiency, the needed data was gathered. They were wanted to produce example of oral performance in semi-structured interview and picture description tasks. The Kruskal-Wallis test pointed that both “negation” and “interrogative” emerge in agreement with the order of acquisition forcasted by Pienemann. In other words, as the participants’ level of proficiency level grew, so did their correct use of interrogatives and negation. Thus, PT is validated for EFL students, too.